Identification and Application of a Rice Senescence-Associated Promoter(1)([C])([W])([OA]) - Liu, Li (American Society of Plant Biologists, 2010)
SAG39 is a rice (Oryza sativa) gene that encodes a cysteine protease. SAG39 shares 55% homology with the Arabidopsis (Arabidopsis thaliana) senescence-associated protein SAG12. The promoter for SAG39 (P(SAG39)) was isolated, and SAG39 expression was determined to be relatively low in mature leaves, while not expressed in the endosperm. SAG39 mRNA levels increased as senescence progressed, with maximum accumulation of transcripts at late senescence stages. Gel retardation assays indicated that two cis-acting elements in P(SAG39), HBOXCONSENSUSPVCHS and WRKY71OS, responded to leaf senescence. To test if P(SAG39) could be useful for increasing rice yields by increasing cytokinin content and delaying senescence, homozygous transgenic plants were obtained by linking P(SAG39) to the ipt gene and introducing it into Zhonghua 11. The chlorophyll level of the flag leaf was used to monitor senescence, confirming the stay-green phenotype in P(SAG39):ipt transgenic rice versus wild-type plants. Changes in the cytokinin content led to early flowering and a greater number of emerged panicles 70 d after germination in the transgenic rice. Measurements of sugar and nitrogen contents in flag leaves demonstrated a transition in the source-sink relationship in transgenic plants triggered at the onset of leaf senescence, with the nitrogen content decreasing more slowly, while sugars were removed more rapidly than in wild-type plants. The importance of these changes to rice physiology, yield, and early maturation will be discussed.